2020
DOI: 10.1016/j.celrep.2020.108289
|View full text |Cite
|
Sign up to set email alerts
|

MutSβ Stimulates Holliday Junction Resolution by the SMX Complex

Abstract: Highlights d MutSb, but not MutSa, interacts directly with SLX4 d MutSb stimulates the resolution of recombination intermediates by SMX d Defects in MutSb lead to the accumulation of unresolved anaphase bridges at mitosis d MutSb is required for efficient Holliday junction resolution and genome stability

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 104 publications
3
26
0
Order By: Relevance
“…Besides inhibition of MMR, an alternative explanation for how SLX4 mediates 6-TG and MNNG resistance could have been through the resolution of HR intermediates formed after MutSa-dependent MMR. In line with this, cells lacking BRCA2 or RAD51 paralogs were previously shown to be hypersensitive to 6-TG or MNNG (59)(60)(61)(62) and MutSb stimulates in vitro the processing of HR intermediates by the SMX complex (26). However, MSH3-deficient cells are not sensitive to 6-TG nor MNNG making this an unlikely explanation (50)(51)(52)(53).…”
Section: )mentioning
confidence: 85%
See 2 more Smart Citations
“…Besides inhibition of MMR, an alternative explanation for how SLX4 mediates 6-TG and MNNG resistance could have been through the resolution of HR intermediates formed after MutSa-dependent MMR. In line with this, cells lacking BRCA2 or RAD51 paralogs were previously shown to be hypersensitive to 6-TG or MNNG (59)(60)(61)(62) and MutSb stimulates in vitro the processing of HR intermediates by the SMX complex (26). However, MSH3-deficient cells are not sensitive to 6-TG nor MNNG making this an unlikely explanation (50)(51)(52)(53).…”
Section: )mentioning
confidence: 85%
“…Hence, SLX4 exerts multiple functions in genome maintenance, each mediated by one or several protein-protein interactions. Intriguingly, the mismatch repair (MMR) factor MSH2 was also identified as a binding partner of human SLX4 (3) but the functional relevance of this interaction remained unexplored until recently (26). The primary role of MMR is to correct replication errors introduced by DNA polymerases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has also shed light on the interaction between SLX4 and the MSH2-MSH3 heterodimer ( Figure 5A ), which has important roles in mismatch repair and homologous recombination ( Svendsen et al, 2009 ; Gonzalez-Prieto et al, 2015 ; Zhang et al, 2019 ; Young et al, 2020 ). Coimmunoprecipitation experiments showed that the interaction between SLX1-SLX4 and MSH2-MSH3 is consistent throughout the cell cycle, suggesting that MSH2-MSH3 may represent an integral component of the SX and SMX complexes ( Young et al, 2020 ). Indeed, MSH2-MSH3 stimulated the ability of SLX1-SLX4 and SMX to cleave Holliday junctions and trinucleotide repeat loops, expanding the repertoire of DNA substrates that are cleaved by SLX4-nuclease complexes ( Young et al, 2020 ).…”
Section: Macromolecular Slx4-complexes: New Players On the Blockmentioning
confidence: 99%
“…Coimmunoprecipitation experiments showed that the interaction between SLX1-SLX4 and MSH2-MSH3 is consistent throughout the cell cycle, suggesting that MSH2-MSH3 may represent an integral component of the SX and SMX complexes ( Young et al, 2020 ). Indeed, MSH2-MSH3 stimulated the ability of SLX1-SLX4 and SMX to cleave Holliday junctions and trinucleotide repeat loops, expanding the repertoire of DNA substrates that are cleaved by SLX4-nuclease complexes ( Young et al, 2020 ). The interplay between SLX4 and MSH2-MSH3 was reviewed recently ( Young and West, 2021 ).…”
Section: Macromolecular Slx4-complexes: New Players On the Blockmentioning
confidence: 99%